Remarkably enhanced direct dissolution of plutonium oxide in task-specific ionic liquid: insights from electrochemical and theoretical investigations. Issue 10 (15th January 2019) - Jayachandran, Kavitha; Gupta, Ruma; Chandrakumar, K. R. S.; Goswami, Dibakar; Noronha, D. M.; Paul, Sumana; Kannan, S.
Abstract : A simple way of catching a big fat element: plutonium from radioactive waste by a task specific ionic liquid. Abstract : The present work envisages an approach for direct dissolution of PuO2 in a task-specific ionic liquid (TSIL). An attractive possibility to electrodeposit plutonium from the mixture of TSIL and PuO2 has been explored further. The carboxyl functional group attached to the TSIL plays a key role in facilitating the dissolution of plutonium ions.